Penerapan Storytelling Digital untuk Menurunkan Kecemasan Pada Anak Prasekolah di Bangsal Melati RSUD Sleman - Sari, Nadia Puspita; Utami, Khristina Dias (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Hospitalization anxiety is an emotional response that arises when children experience fear, discomfort, or stress during hospital care. Digital storytelling therapy is a non-pharmacological technique that can help reduce anxiety levels, especially during vital signs examination. Purpose: To determine the effect of digital storytelling therapy on reducing anxiety levels in preschool children during vital signs examination in the Melati Ward of Sleman Regional Public Hospital. Method: This study employed a case study design involving a preschool-aged child (An. A) who experienced hospitalization anxiety. Anxiety levels were measured using the (DASS-42), which was completed by the parent based on observations of the child’s behavioral and emotional responses during vital signs examination. Instrument adaptation was conducted by adjusting the DASS statements into behavioral indicators of anxiety in preschool children, including crying, tense facial expressions, restlessness, refusal of procedures, and the level of cooperation during examination. Result: The results of the case study showed a decrease in anxiety levels after the implementation of digital storytelling therapy. The anxiety score on the first day was 12 (moderate anxiety), which decreased to 8 (mild anxiety) on the second day and to 4 (mild anxiety) on the third day. Conclusion: Digital storytelling therapy is effective in reducing hospitalization anxiety in preschool-aged children.